Generative adversarial imitation learning with bird?s-eye view input generation for autonomous driving on urban environments - Couto, Gustavo Claudio Karl (2023)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2023.